BATAS-BATAS PERGAULAN ANTARA LELAKI DAN PEREMPUAN DALAM MASYARAKAT ISLAM KINI: SATU HURAIAN HUKUM ISLAM SEMASA - Ab Ghani, Anisah (Jurnal Syariah, 2019)
This article reviews Islamic rulillg (hukrn) cOllcernillg lawful and unla wjid interaction between mell and womell in general. It emphasizes two aspects of hukl1l related to Muslim womell: prohibited and the other is permitted. This permissible interaction is well explained referring to cases involved Muslim womell in current situation.